Real-time intelligent colorimetric paper indicator based on a mulberry-derived anthocyanin for monitoring aquatic products freshness - Guangxin Yang; Junyu Zhang; Yifan Zhao; Lin Gu; Peng Wang; Chengqi Fan; Hai Chi; Cong Kong (Food Packaging and Shelf Life, 2026)

The role of macrophage-myofibroblast transition in the pathogenesis of multi-organ fibrosis - Congcong Guo; Ran Cao; Lin Liao; Junyu Zhao; Tianzuo Wang; Junhan Li; Yue Zhang; Haotian Li (Tissue and Cell, 2026)

Durable and efficient 2D/3D perovskite bulk heterojunction solar cells via BA2MAPb2I7 single crystal addition - Zihong Cai; Xin Chen; Zixing Guo; Yafei Wang; Tianqi Niu; Junyu Lin; Shihai Ye; Qianqiu Guan; Jiazhen Xu; Jiale Huang; Tao Zou; Zuoshan Zhang; et al. (Chemical Engineering Journal, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Erratum to “The role of macrophage-myofibroblast transition in the pathogenesis of multi-organ fibrosis” [Tissue Cell 103 (2026) 103702] - Congcong Guo; Ran Cao; Lin Liao; Junyu Zhao; Tianzuo Wang; Junhan Li; Yue Zhang; Haotian Li (Tissue and Cell, 2026)

Performance enhancement of demisters with orifice baffles: A study on separation efficiency and flow mechanism - Junyu Tao; Yuze Dong; Yuanming Ding; Zhe Lin; Zuchao Zhu (Desalination, 2026)

Simultaneous inactivation of Microcystis aeruginosa and degradation of microcystin-LR via a p-p ZnCo2O4/Cu2O S-scheme photocatalyst: Mechanism and “Adsorption-Oxidation-Lysis” pathway - Jie Zhang; Junyu Lu; Mingcan Wu; Qingshan Xu; Shu Lin; Kezhen Qi (Bioresource Technology, 2026)

Agmatine induces mitophagy via the PTS-I2R pathway to increase autophagic flux and attenuate sepsis-induced intestinal epithelial cell apoptosis - He Jin; Shuangqin Yin; Yongming Li; Xiangwei Hou; Lin Qiao; Tianyin Kuang; Jing Zhou; Xue Yang; Wanting Zeng; Chao Fan; Li Luo; Lihui Wang; et al. (Inflammation Research, 2026)

Coupling upconversion effect with p-n heterojunction on TiAl6V4 to eradicate bacterial biofilms - Keyi Yao; Lixuan Huang; Jie Shao; Junyu Dong; Junhua Xu; Yongsheng Liu; Sze Wing Cheung; Lin Xiang; Xuemei Zhou (Chemical Engineering Journal, 2026)

Mutual information guided domain adaptation network for unsupervised transfer fault diagnosis of offshore wind turbines under time-varying conditions and scarce labels - Yun Kong; Guoyu Huang; Cuiying Lin; Haiqiang Wang; Qinkai Han; Junyu Qi; Hui Liu; Fulei Chu (Ocean Engineering, 2026)

Peimisine-sulfide improves inflammation caused by copper sulfate through inhibiting ferroptosis using zebrafish embryos - Siyu Chen; Junyu Liang; Tingting Lin; Zitong Huang; Leyan Huang; Liang Bu; Chuanzhi Kang; Chengyong He (Journal of Environmental Sciences, 2026)

Strain-specific impacts of Pichia kudriavzevii on metabolite profiles and microbial community dynamics in Chinese Baijiu fermentation: Integrated metabolomics and metagenomics analysis - Boqin Zhang; Mengbo Wang; Jia Zheng; Chenxi Yu; Chunhui Wei; Junyu Ren; Shouying Sun; Guoming Wang; Jinhua Wang; Yanping Lu; Liangcai Lin; Cuiying Zhang (International Journal of Food Microbiology, 2026)

Dual-halide solid electrolyte interphase engineering with MXene enables dense (110)-oriented Li deposition for high-performance Li metal anodes - Zongyu Mao; Shuaihe Zhang; Ye Han; Yujing Xu; Shuxin Xie; Bei Huang; Shuaihong Chen; Xintong Cai; Junyu Lin; Xiao Yu; Shaozhong Zeng; Dongju Fu; et al. (Chemical Engineering Journal, 2026)

Pearl River Estuary Shelf Elements Reveal Asynchronous Enhanced Human Activities During Late Holocene in South China - Meng Tang; Rou Wen; Junyu Lin; Liang Chen; Zhenyu Mao; Mingkun Li (Journal of Marine Science and Engineering, 2026)
Human-driven soil erosion is a signal of the widely debated “Anthropocene”. There is widespread controversy regarding the time consistency and time transgression of human-driven soil erosion in the Late Holocene. In this study, three well-dated cores, B10, B14 and W20 from west to east, spanning the past 4–6 ka from the Pearl River Estuary (PRE) shelf, southern China, were selected for elemental tests. Principal component analysis divides the elements into four components. The first principal component (PC1) includes TFe2O3, Al2O3, V, Cs, Rb, Ga, TiO2, K2O, Ta, Nb, MnO, Th, LOI, and Cl, being the proxy for fine-grained terrigenous input and watershed soil erosion. The PC1 variations in B10 and B14 reveal that erosion enhanced at ~2.2 ka BP, and less erosion occurred at ~1.5 ka BP but has intensified since ~1.2 ka BP, which is consistent with the simulated cropland area of the Pearl River Basin and lake records in the upper West River, southwestern China. However, the records from the W20 reveal a continuous increase in terrestrial input since 2.2 ka BP, which is consistent with the soil erosion changes recorded by the South China coast lakes at its provenance region. Hence, differences in the initial age of the signals of human activities were revealed in the PRE shelf system. Our study not only reveals the time transgression of the “Anthropocene” boundary but also updates the sediment source-to-sink model of the PRE shelf system.

Enhancing thermospheric density modeling using bias factor analysis - Yao Wu; Junyu Chen; Chusen Lin; Zijie Li; Yaobin Fang; Yu Wu (Advances in Space Research, 2026)

Investigation on the FCNN-based propeller optimization constrained by cavitation performance - Junyu Ge; Haipeng Guo; Guangnian Li; Lin Du (Ocean Engineering, 2026)

Oxygen doping regulates coordination structure of iron-single-atom catalysts for peroxymonosulfate activation and pollutants degradation: high-valent iron-oxo species role - Lin Niu; Qitao Lei; Zhi Tang; Yaqi Cai; Junyu Wang; Guoqing Hou; Xiaoli Zhao; Fengchang Wu (Chemical Engineering Journal, 2026)

Associations of Iron Indicators with Cognitive Impairment Risk in Postmenopausal Women: Evidence from a Matched Case–Control Study and Back Propagation Neural Network Model - Wanting Chao; Peiyi Liu; Junyu Li; Yudan Hao; Huijun Zhou; Lijie Feng; Shasha Ruan; Xifei Yang; Jianjun Liu; Yankui Lin; Xian Wang (Molecular Neurobiology, 2026)

Blocking T-type calcium channels disrupts spermatogenesis in vivo and adversely affects spermatocytes in vitro by impairing mitochondrial function and autophagic flux - Xiuling Zhao; Lei Wang; Shiqin Huang; Lin Liu; Xiaorong Wang; Liping Pu; Hao Chen; Junyu Nie (Reproductive Toxicology, 2025)

Magnetic mineral dissolution front delimited by late Holocene sediment accumulation acceleration in the inner shelf, northern South China Sea - Mingkun Li; Meng Tang; Liang Chen; Yongying Zeng; Rou Wen; Junyu Lin; Mingjie Yu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Integrative transcriptomics and QTL analysis identify lactoperoxidase and deubiquitinase as key targets for mastitis control in dairy animals - Jie Su; Fei Wang; Runshi Li; Lin Guo; Xianghai Ma; Xiaoyan Wang; Junyu Zhang; Shuaitao Lian; Jiaoxiong Xue; Jianglin Zhao; Yong Zhang; Xu Liu; et al. (Food Bioscience, 2025)

An integrated multi-algorithm analysis to decipher senescence and metabolic characteristics in nucleus pulposus cells during disc degeneration - Zhuangyao Liao; Ming Li; Ziyu Chen; Zhi Yao; Yuluan Wu; Zhen Tan; Junyu Qian; Chunyuan Yang; Lin Huang; Lixiang Xue; Deli Wang (GeroScience, 2025)
Accumulating evidence has suggested that intervertebral disc degeneration (IVDD) serves as a health problem deserving attention from worldwide, owing to the low back pain and even disability it causes. Cellular senescence, an irreversible process of terminal cell cycle arrest, plays an essential role in the degeneration of nucleus pulposus (NP) cells and IVDD with an unknown underlying mechanism. Here, we have explored the senescence signature in IVDD through high dimensional weighted gene co-expression network analysis (hdWGCNA) algorithm in two single cell datasets (PRJCA014236 and GSE244889) to construct a novel signature called NP_Senescence, which accurately identifies the patients with IVDD. The efficacy and accuracy were validated in various external datasets, including two expression array datasets (GSE70362 and GSE34095) and one single cell dataset (GSE230809). Additionally, the accuracy of the specific model was also verified with the senescent cell identification (SenCID) algorithm. IVDD patients with a high NP_Senescence score exhibited the characteristics of compensated activation of hyaluronic acid monomers synthesis and abnormal status of DNA damage repair through single-cell Flux Estimation Analysis (scFEA) algorithm. Furthermore, the NP_Senescence was negatively associated with the level of AMP and Glucose-1-phosphate, while positively associated with the level of β-alanine and UDP-glucuronic acid. In conclusion, we constructed a novel disc-specific scoring model NP_Senescence by comprehensively analyzing the senescence-related genes of IVDD, which can be used for patient early diagnosis and treatment, as well as the identification of metabolic characteristics.

Bending behaviour of rigid-flexible combined inflatable membrane structures for floating bridge modules - Yunling Ye; Jin Gan; Huabing Liu; Weiguo Wu; Lin Wang; Junyu Guo; He Li (Ocean Engineering, 2025)

Developmental exposure to echimidine induces locomotor hyperactivity in zebrafish larvae via inhibiting acetylcholinesterase activity - Tingting Lin; Siyu Chen; Yingyi Ren; Junyu Liang; Zhenghong Zuo; Zhiqiang Luo; Jian Yang; Chengyong He (Journal of Environmental Sciences, 2025)

The physiological effects of intrinsic and isolated arabinoxylans on human immunometabolic response: A systematic review and meta-analysis - Shanshan Jiang; Chenxi Cai; Edward C. Deehan; Junyu Chen; Changcan Feng; Mingyue Yang; Zhongming Weng; Jiahui Long; Jiaxuan Xie; Shan Lin; Guiling Li; Jian Li; et al. (Food Research International, 2025)

Intestinal barrier disruption by cadmium and microplastics: Mechanistic insights from integrated metabolomic and proteomic analysis in mice - Jiajie Yang; Danni Wang; Junyu Huang; Ting Zhao; Maoting Chen; Shengxuan Lin; Xinqi Yu; Falong Yang; Haifeng Liu; Shiwen Xu; Dechun Chen (Environmental Pollution, 2025)

Controlled release of caffeine from oat globulin nanocomplexes: Biocompatibility and gastrointestinal dynamics - Junyu Lin; Hanhan Liu; Jianyu Yang; Yang Gao; Guanghua Zhao; Chenyan Lv (Food Chemistry, 2025)

Synergistic enhancement of thermoelectric performance in SnTe via Bi and Ge Co-doping - Minwen Yang; Jingyi Lyu; Junyu Lin; Yanqi Huang; Zehao Lin; Rui Zhang; Jing Shuai; Yanglong Hou (Chemical Engineering Journal, 2025)

Insights into soil carbon metabolism and carbon sequestration capacity under organic fertilizer substitution model - Zirui Zhou; Yan Liao; Qian Zhang; Zicong Xiong; Junwei Tang; Jing Tian; Xiaolong Chang; Huailin Zhang; Junyu Xiang; Ziyuan Lin; Chaolan Zhang (Applied Soil Ecology, 2025)

Correction: Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)

Histopathological Insights into Demyelination and Remyelination After Spinal Cord Injury in Non-human Primates - Junhao Liu; Zucheng Huang; Kinon Chen; Rong Li; Zhiping Huang; Junyu Lin; Hui Jiang; Jie Liu; Qingan Zhu (Neuroscience Bulletin, 2025)

Comparative study on combustion characteristics of biomass digestate-derived pyrochar and hydrochar: Insights from structural composition and oxygen-containing groups - Haifeng Wen; Jixin Li; Xin Wang; Wei Mao; Yiyang He; Xiao Cao; Haiyan Yang; Junyu Zhang; Suyun Xu; Lin Gu (Fuel, 2025)

Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)
Laminated Diatom Mats (LDMs) in the low-latitude Western Pacific provide key insights into global climate and carbon cycling. While Ethmodiscus rex ( E. rex ) LDMs research has advanced, two critical aspects remain to be elucidated: (1) the precise chronology of LDMs formation, and (2) its relationship with oceanic circulation patterns and associated nutrient flux variations. In this study, we employed AMS 14 C dating coupled with carbonate content variations to constrain the formation age of LDMs, complemented by comprehensive geochemical and clay mineral analyses of core E20, we found: (1) Diatom blooms occurred mainly from Last Glacial Maximum (LGM) to early Holocene; (2) Sediments are mostly volcanic, with increased material in E. rex layers suggesting stronger deep currents transported volcanic debris; (3) Blooms weren’t solely caused by Asian dust-derived nutrients. We propose deep current intensification and topographic upwelling drove diatom growth, highlighting deep ocean processes’ role in surface productivity and LDMs formation. This advances understanding of their climate and carbon cycle significance.

Eggshell-inspired heterogeneous bilayer paper window with selective gas permeability for preserving fresh produce - Lin Peng; Junyu Chen; Yongye Chen; Azadeh Nilghaz; Xueyan Yun; Xiaofang Wan; Huanhuan Zhan; Junfei Tian (Chemical Engineering Journal, 2025)

Mutation Screening of ATXN1, ATXN2, and ATXN3 in Amyotrophic Lateral Sclerosis - Tianmi Yang; Qianqian Wei; Dejiang Pang; Yangfan Cheng; Jingxuan Huang; Junyu Lin; Yi Xiao; Qirui Jiang; Shichan Wang; Chunyu Li; Huifang Shang (Molecular Neurobiology, 2025)

Motor-Cognitive Dual-Task Cost and Associated Micro Lesions of Cerebellum and Brainstem in Multiple System Atrophy (Parkinsonian Type) - Yi Xiao; Shichan Wang; Yanbing Hou; Junyu Lin; Tianmi Yang; Qirui Jiang; Jiyong Liu; Ruwei Ou; Chunyu Li; Huifang Shang (The Cerebellum, 2025)

Research on LSTM-PPO Obstacle Avoidance Algorithm and Training Environment for Unmanned Surface Vehicles - Wangbin Luo; Xiang Wang; Fang Han; Zhiguo Zhou; Junyu Cai; Lin Zeng; Hong Chen; Jiawei Chen; Xuehua Zhou (Journal of Marine Science and Engineering, 2025)
The current unmanned surface vehicle (USV) intelligent obstacle avoidance algorithm based on deep reinforcement learning usually adopts the mass point model to train in an ideal environment. However, in actual navigation, due to the influence of the ship model and the water surface environment, the training set is triggered. The reward function does not match the actual situation, resulting in a poor obstacle avoidance effect. In response to the above problems, this paper proposes a long and short memory network-proximal strategy optimization (LSTM-PPO) intelligent obstacle avoidance algorithm for non-particle models in non-ideal environments, and designs a corresponding deep reinforcement learning training environment. We integrate the motion characteristics of the unmanned boat and the influencing factors of the surface environment, based on the curiosity-driven set reward function, to improve its autonomous obstacle avoidance ability, combined with the LSTM network to identify and save obstacle information to improve the adaptability to the unknown environment; virtual simulation is performed in Unity. The engine builds a USV physical model and a refined water deep reinforcement learning training environment including a variety of obstacle models. The experimental results demonstrate that the LSTM-PPO algorithm exhibits an effective and rational obstacle avoidance effect, with a success rate of 86.7%, an average path length of 198.52 m, and a convergence time of 1.5 h. A comparison with the performance of three other deep reinforcement learning algorithms reveals that the LSTM-PPO algorithm exhibits a 21.5% reduction in average convergence time, an 18.5% reduction in average path length, and an approximately 20% enhancement in the success rate of obstacle avoidance in complex environments. These results indicate that the LSTM-PPO algorithm can effectively enhance the search efficiency and optimize the path planning in obstacle avoidance for unmanned boats, rendering it more rational.

Canagliflozin reverses doxorubicin-induced cardiotoxicity via restoration of autophagic homeostasis - Jianping Luo; Mingyuan He; Changzhu Liang; Xiaoxia Huang; Yingqi Zhu; Donghong Hu; Junyu Yan; Mingjue Li; Hairuo Lin; Wangjun Liao; Jianping Bin; Ziyun Guan; et al. (Toxicology and Applied Pharmacology, 2025)

Improving physicochemical properties and gel formation mechanism of nutty plant-based yogurt with Tremella fuciformis polysaccharides - Ling Lin; Xiaoqing Qian; Junyu He; Yuting Shao; Yao Zeng; Mengxin Tang; Yong Fang; Xiaoyi Jiang; Jian Ding (Food Chemistry, 2025)

Optimization of low-earth orbit density model based on support vector regression - Yao Wu; Junyu Chen; Chusen Lin; Zijie Li (Advances in Space Research, 2025)

Phaeobacter italicus JN-W1: A pathogenic bacterium causing bleaching disease in Porphyra sensu lato (Bangiales, Rhodophyta) - Qiqin Liu; Hanmeng Shi; Rui Yang; Junyu Lin; Juanjuan Chen; Haimin Chen (Aquaculture, 2025)

Reactive oxygen species-sensitive fenofibrate-loaded dextran nanoparticles in alleviation of osteoarthritis - Weibei Sheng; Shuai Liao; Siyang Cao; Yihao Wei; Jin Zhao; Yaohang Yue; Haotian Qin; Tiantian Qi; Junyu Qian; Jianjing Lin; Jian Weng; Yingqi Chen; et al. (Carbohydrate Polymers, 2025)

A method for compensating prediction errors to improve the orbit prediction accuracy of Starlink satellites - Chusen Lin; Junyu Chen; Haoze Zhu (GPS Solutions, 2025)

Comparison of recombinant protein Z with natural protein Z derived from malt: From structure to functional properties - Hanhan Liu; Kailin Yang; Yang Gao; Junyu Lin; Guanghua Zhao; Chenyan Lv (Food Chemistry, 2024)

Novel ternary deep eutectic solvents pretreatment of corn stalk to realize high-value utilization - Zhiwen Jia; Xinlong Li; Shibo Xu; Yan Sun; Lin Chen; Jiamin Ye; Wanyu Li; Tao Wu; Junyu Li; Shiyang Wang; Xiwei Xu (Chemical Engineering Journal, 2024)

Atomically dispersed Fe-N4 sites in activation of peroxymonosulfate for wastewater purification: Mechanism of non-radical pathways and their quantification - Lin Niu; Zhi Tang; Qitao Lei; Yaqi Cai; Junyu Wang; Deyi Hou; Xiaoli Zhao; Fengchang Wu (Chemical Engineering Journal, 2024)

Effects of stepwise depressurisation rate on methane hydrate dissociation dynamics at pore scale using microfluidic experiments - Junyu Yang; Qianghui Xu; Boyu Huang; Yizhe Liu; Zhiying Liu; Le Zhang; Kai H. Luo; Lin Shi (Gas Science and Engineering, 2024)

Intelligent technologies powering clean incineration of municipal solid waste: A system review - Junyu Tao; Zaixin Li; Chao Chen; Rui Liang; Shuang Wu; Fawei Lin; Zhanjun Cheng; Beibei Yan; Guanyi Chen (Science of The Total Environment, 2024)

Pore-scale visualization of hydrate dissociation and mass transfer during depressurization using microfluidic experiments - Junyu Yang; Yizhe Liu; Qianghui Xu; Zhiying Liu; Xiaoye Dai; Lin Shi; Kai H. Luo (Fuel, 2024)

GTFE-Net-BiLSTM-AM: An intelligent feature recognition method for natural gas pipelines - Lin Wang; Cheng Hu; Tingxia Ma; Zhongfeng Yang; Wannian Guo; Zhihao Mao; Junyu Guo; He Li (Gas Science and Engineering, 2024)

Rare DNAJC7 Variants May Play a Minor Role in Chinese Patients with ALS - Shichan Wang; Xiaoting Zheng; Qianqian Wei; Junyu Lin; Tianmi Yang; Yi Xiao; Qirui Jiang; Chunyu Li; Huifang Shang (Molecular Neurobiology, 2024)

Molecular insight into the vertical migration and degradation of dissolved organic matter in riparian soil profiles - Chang Liu; Lin Li; Yue Zhi; Junyu Chen; Qingyang Zuo; Qiang He (Environmental Research, 2024)

The Influence of Seamounts on the Enrichment of Rare Earth Elements in Sediments—A Case Study of the Marcus-Wake Seamounts in the Western Pacific Ocean - Tinglu Xiao; Dong Xu; Tao Deng; Junyu Lin; Liming Ye; Qian Ge; Xibin Han; Yanhui Dong; Fengyou Chu (Journal of Marine Science and Engineering, 2024)
Deep-sea sediments enriched in rare earth elements and yttrium (REY-rich sediments) are widely distributed on the deep-sea floor, and their formation mechanism remains elusive. Although studies have recognized the link between seamounts and REY-rich sediments, in-depth analysis of the specific roles and effects of seamounts in the formation of REY-rich sediments is lacking. In this study, we analyzed surface sediments from the Marcus-Wake Seamounts for grain size, geochemistry, and mineral composition and classified the samples into three types: samples with moderate REY content and dominated by terrestrial detritus; samples with high REY and authigenic mineral content; and samples rich in CaCO3 but poor in REY. The REY in the sediments of the study area partly originate from Asian dust input and partly from seawater and/or pore water, and are mainly enriched in REY carrier particles including bioapatite fossils and micronodules. The amount of REY carrier particles influences the REY content in the sediments. The current field, primary productivity, weathering process, and depositional environment around seamounts are different from those of abyssal plains, which are conducive to the formation of REY-rich sediments. Strong bottom currents may exist in the southeastern direction of some large seamounts (e.g., Niulang Guyot), leading to the selective accumulation of REY-rich bioapatite fossils and micronodules, resulting in the formation of REY-rich sediments.

Numerical modeling on nuclide transport around a nuclear waste repository under coupled thermo-hydro-mechanical condition - Jintong Zhang; Junyu Chen; Zhihong Zhao; Sicong Chen; Guihong Liu; Xingguang Zhao; Ju Wang; Tao Lin; Bing Liu (Computers and Geotechnics, 2023)

Seismic behavior and design method of seawater sea-sand concrete reinforced with GFRP and five interlocking spirals - Zhe Xiong; Jinhu Zheng; Zepeng Chen; Yubiao Huang; Zhimin Wang; Junyu Chen; Lianghao Lin; Lijuan Li; Sihua Qiao; Feng Liu (Engineering Structures, 2023)

Protective effect of solanesol in glucose-induced hepatocyte injury: Mechanistic insights on oxidative stress and mitochondrial preservation - Yiqiu Liu; Musen Lin; Xingrui Mu; Lin Qin; Junyu Deng; Ye Liu; Xingqian Wu; Wenjie He; Huiwen Pang; Felicity Han; Chengxin Sun; Xuqiang Nie (Chemico-Biological Interactions, 2023)

Risk assessment of predatory lady beetle Propylea japonica's multi-generational exposure to three non-insecticidal agrochemicals - Guofeng Chang; Hui Xue; Jichao Ji; Li Wang; Xiangzhen Zhu; Kaixin Zhang; Dongyang Li; Xueke Gao; Lin Niu; Mengxue Gao; Junyu Luo; Jinjie Cui (Science of The Total Environment, 2023)

EIF4A3-Induced Exosomal circLRRC8A Alleviates Granulosa Cells Senescence Via the miR-125a-3p/NFE2L1 axis - Jie Xing; Mengxue Zhang; Shijie Zhao; Mingjun Lu; Li Lin; Lu Chen; Wujiang Gao; Wenxin Li; Junyu Shang; Jiamin Zhou; Xiaolan Zhu (Stem Cell Reviews and Reports, 2023)
Premature ovarian failure (POF) is an important cause of female infertility and seriously impacts the physical and psychological health of patients. Mesenchymal stromal cells-derived exosomes (MSCs-Exos) have an essential role in the treatment of reproductive disorders, particularly POF. However, the biological function and therapeutic mechanism of MSCs exosomal circRNAs in POF remain to be determined. Here, with bioinformatics analysis and functional assays, circLRRC8A was found to be downregulated in senescent granulosa cells (GCs) and acted as a crucial factor in MSCs-Exos for oxidative damage protection and anti-senescence of GCs in vitro and in vivo. Mechanistic investigations revealed that circLRRC8A served as an endogenous miR-125a-3p sponge to downregulate NFE2L1 expression. Moreover, eukaryotic initiation factor 4A3 (EIF4A3), acting as a pre-mRNA splicing factor, promoted circLRRC8A cyclization and expression by directly binding to the LRRC8A mRNA transcript. Notably, EIF4A3 silencing reduced circLRRC8A expression and attenuated the therapeutic effect of MSCs-Exos on oxidatively damaged GCs. This study demonstrates a new therapeutic pathway for cellular senescence protection against oxidative damage by delivering circLRRC8A-enriched exosomes through the circLRRC8A/miR-125a-3p/NFE2L1 axis and paves the way for the establishment of a cell-free therapeutic approach for POF. CircLRRC8A may be a promising circulating biomarker for diagnosis and prognosis and an exceptional candidate for further therapeutic exploration. Graphical Abstract

Construction of a risk model based on N6-methyladenosine-related lncRNAs for predicting the prognosis of breast cancer - Wenxia Cui; Jiasheng Zhang; Junyu Lin; Sunwang Xu; Lingjun Kong; Wei Lin; Jiajie Xue; Qingshui Wang; Yao Lin; Youzhi Zhu (Journal of Biosciences, 2023)

Genetic and Phenotypic Spectrum of Amyotrophic Lateral Sclerosis Patients with CCNF Variants from a Large Chinese Cohort - Bi Zhao; Qirui Jiang; Junyu Lin; Qianqian Wei; Chunyu Li; Yanbing Hou; Bei Cao; Lingyu Zhang; Ruwei Ou; Kuncheng Liu; Tianmi Yang; Yi Xiao; et al. (Molecular Neurobiology, 2023)
Cyclin F (CCNF) variants have been found to be associated with amyotrophic lateral sclerosis (ALS)/frontotemporal dementia (FTD). However, the genetic and clinical characteristics of ALS patients who carry CCNF variants are largely unknown. Genetic analysis was performed for 1587 Chinese ALS patients, and missense variants were predicted by software analyses. Additionally, we searched PubMed, Embase, and Web of Science for relevant literature and conducted a meta-analysis of the frequency of variants. In our ALS cohort, we identified 29 nonsynonymous variants in 41 ALS patients. Among these ALS patients, 18 (1.1%) were carriers of 15 rare missense variants that were considered probably pathogenic variants, and 11 of 15 variants were novel. Seven relevant studies were identified, and a total of 43 CCNF variants in 59 ALS patients with a frequency of 0.8% were reported. The ratio of males to females in our cohort (10/8) was similar to that in Caucasian populations (4/7) and significantly higher than that in Asian populations (10/1). The proportion of bulbar onset in Caucasian CCNF carriers was similar to our cohort (25.0 vs. 27.8%); however, bulbar onset had never been reported in previous Asian studies (0/11). FTD was not found in CCNF carriers in previous Asian studies and our cohort, but it has been reported in a FALS cohort (1/75) of Caucasian individuals. There were some differences in the clinical characteristics among different ethnic ALS populations. More basic scientific studies are needed to elucidate the pathogenic mechanisms and genotype-phenotype associations of CCNF variants.

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Development of a low-density SNP genotyping panel by a novel technology mGPS and its application in germplasm identification of abalone - Weihong Lin; Qizhen Xiao; Feng Yu; Zhaofang Han; Junyu Liu; Wenzhu Peng; Zekun Huang; Yuting Lei; Weiguo Li; Weiwei You; Xuan Luo; Caihuan Ke (Aquaculture, 2023)

Water quality criteria and ecological risk assessment of lead (Pb) in China considering the total hardness of surface water: A national-scale study - Weigang Liang; Xiaolei Wang; Xiao Zhang; Lin Niu; Junyu Wang; Xia Wang; Xiaoli Zhao (Science of The Total Environment, 2023)

Transgenic Bt cotton expressing Cry1Ac/1Ab does not have detrimental effects on the predator Arma chinensis through its prey Helicoverpa armigera - Yamin Ma; Meng Zhang; Junyu Luo; Jichao Ji; Xiangzhen Zhu; Li Wang; Kaixin Zhang; Dongyang Li; Jinjie Cui; Lin Niu (Journal of Pest Science, 2023)

Important But Overlooked Potential Risks of Substituted Polycyclic Aromatic Hydrocarbon: Looking Below the Tip of the Iceberg - Xiao Zhang; Xiaolei Wang; Xiaoli Zhao; Zhi Tang; Weigang Liang; Xiaowei Wu; Junyu Wang; Xia Wang; Lin Niu (Reviews of Environmental Contamination and Toxicology, 2022)

Application of solid-phase extraction based on magnetic nanoparticle adsorbents for the analysis of selected persistent organic pollutants in environmental water: A review of recent advances - Aiming Wu; Xiaoli Zhao; Junyu Wang; Zhi Tang; Tianhui Zhao; Lin Niu; Wenqiang Yu; Chunyan Yang; Mengyuan Fang; Hongzhou Lv; Shasha Liu; Fengchang Wu (Critical Reviews in Environmental Science and Technology, 2021)

Neuroligins Differentially Mediate Subtype-Specific Synapse Formation in Pyramidal Neurons and Interneurons - Qiang-Qiang Xia; Jing Xu; Tai-Lin Liao; Jie Yu; Lei Shi; Jun Xia; Jian-Hong Luo; Junyu Xu (Neuroscience Bulletin, 2019)

Clinical relationships between the rs2212020 and rs189897 polymorphisms of the ITGA9 gene and epithelial ovarian cancer - Jinyang Liu; Ting Liu; Lin Liang; Junyu He; Manying Zhang; Yanshan Ge; Shan Liao; Yanhong Zhou; Keqiang Zhang (Journal of Genetics, 2019)

Identification of genetic loci conferring partial resistance to southern corn rust through a genome-wide association study - Guangfei Zhou; Derong Hao; Yuxiang Mao; Qiuli Zhu; Guoqing Chen; Huhua Lu; Mingliang Shi; Xiaolan Huang; Zhenliang Zhang; Junyu Zhao; Lin Xue (European Journal of Plant Pathology, 2018)